Validation of the Weight Bias Internalization Scale for Mainland Chinese Children and Adolescents - Chen, Hao; Ye, Yi-duo (Frontiers in Psychology, 2021)
Weight stigma internalization among adolescents across weight categories lead to adverse psychological consequences.The aim of this study is to develop and validate a Chinese version of the Weight Bias Internalization Scale for Chinese adolescents(C-WBIS). A total of 464 individuals aged 9 to 15 years participate in the present study. Based on item response theory (IRT) and classical test theory (CTT), we select the items for the C-WBIS and evaluate reliability, validity. The item response theory yields support for the one-dimensional factor mode. All item parameters fit the IRT model (albeit within an adequate range),8 items are adopted. No evidence of significant Differential item functioning (DIF) was found for gender, age group. The C-WBIS was correlated with the Core Self-Evaluation Scale (CSES) and two subscales of the Social Anxiety Scale for Children (SAS), which indicated an acceptable criterion‐related validity.The C-WBIS is a reliable and valid measure that can be used as a psychometrically sound and informative tool to assess weight bias internalization among adolescents.